Corporate finance - Vlachý, Jan, 1964- (Praha : Leges, 2025)
Based on thorough research, as well as extensive professional and academic experience, the author develops the topic of corporate financial management from its essential theoretical foundations towards a systematic framework, facilitating solution of various decision-making problems in the business domain using a common value-based framework. The second edition has been substantially revised and updated. The approach is innovative in providing a generalized perspective, avoiding the pitfalls of localization for a mobile international readership, using a comparative approach to highlighting and annotating major differences in terminology, conventions and institutions. It will therefore be useful for professionals in an international environment, as well as for education in international study programmes. An exercise book containing 200 problems to practice all the topics is available under the Creative Common licence as an e-book, referenced in the book.
Monografie rozvíjí problematiku podnikových financí od základních teoretických východisek po systematický a hodnotově zaměřený rámec, vhodný pro řešení různých problémů podnikové praxe. Autor přitom vychází z důkladného výzkumu a rozsáhlé odborné i akademické praxe. Druhé vydání je aktualizované a výrazně přepracované. Kniha je mimořádná v tom, že nabízí univerzální pohled bez národní lokalizace, přičemž uvádí a porovnává podstatné rozdíly v terminologii, zvyklostech a institucionálním rámci. Je tak vhodná zejména pro odborníky působící v mezinárodním prostředí, stejně jako pro vysokoškolskou výuku v mezinárodních studijních programech. Ke knize je dostupná cvičebnice s dvěma stovkami příkladů k procvičení všech témat, zpracovaná jako e-kniha a publikovaná v licenci Creative Commons (odkaz najde čtenář v knize).
Obsahuje bibliografické odkazy
Keywords: finance podniku; finanční management; monografie; business finance; financial management; monographs